2018
DOI: 10.1002/mnfr.201800646
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Gluten–Chitosan Interlocked Self‐Assembled Supramolecular Architecture Reduces T‐Cell‐Mediated Immune Response to Gluten in Celiac Disease

Abstract: Scope The prevalence of celiac disease has increased since the last half of the 20th century and is now about 1% in most western populations. At present, people who suffer from celiac disease have to follow a gluten‐exclusion diet throughout their lives. Compliance to this restrictive diet is demanding and the development of alternative strategies has become urgent. Methods and results In this context, it is found that the biocompatible aminopolysaccharide chitosan imposes a different gluten reorganization aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The maximum size sieving permitted by chromatography columns is around 1 × 10 6 Da, whereas polymer Mw higher than 1 × 10 7 g/mol have been reported for GPPs [19,20]. The A4F-MALLS of GPP was used in several approaches, such as studying the quality stability of hybrid wheats over different environments [21], the influence of ozone treatment on wheat proteins and quality [22], or the effect of chitosan treatment on gluten proteins [23]. Using A4F-MALLS the influence of the genetic and/or environmental factors have initially reported [20] by studying in a limited set of cultivars grown on two years multilocal trials in France.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum size sieving permitted by chromatography columns is around 1 × 10 6 Da, whereas polymer Mw higher than 1 × 10 7 g/mol have been reported for GPPs [19,20]. The A4F-MALLS of GPP was used in several approaches, such as studying the quality stability of hybrid wheats over different environments [21], the influence of ozone treatment on wheat proteins and quality [22], or the effect of chitosan treatment on gluten proteins [23]. Using A4F-MALLS the influence of the genetic and/or environmental factors have initially reported [20] by studying in a limited set of cultivars grown on two years multilocal trials in France.…”
Section: Introductionmentioning
confidence: 99%
“…The strategy of the supramolecular assembly was successful in decreasing gluten digestibility and its capacity to stimulate a T-cell-mediated immune response. This type of tunable approach is a promising nanotechnology tool to change biomaterials features as their immunogenicity [93].…”
Section: Alv003mentioning
confidence: 99%
“…More recently, it was showed that the interaction between gluten proteins and the aminopolyssacharide chitosan imposes a different gluten reorganization resulting in novel supramolecular structures. This novel supramolecular architecture decreased gluten digestibility, TG2 activity and the ability of gluten to stimulate a T-Cell-mediated immune response [ 12 , 40 ].…”
Section: Polyphenols-gluten Interaction: Sequestering Of Celiac-rementioning
confidence: 99%
“…In this context, alternative approaches need to be addressed to overcome the biopsychosocial burden in celiac disease [ 11 ]. Some promising approaches took the advantage of knowing the primary trigger of celiac disease, the gluten, and tried to detoxify it: by means of genetic modification as the genetically modified low-gliadin wheat lines, using gluten specific proteases to deliver a complete digestion of immunogenic peptides, using microbial transglutaminase to hamper the deamidation process performed by tissue transglutaminase (TG2) [ 5 ] and even through the sequestration of gliadin proteins or peptides by a novel gluten molecular re-organization [ 12 ] or after ingestion by the use of synthetic polymeric binders in order to decrease gliadin digestibility [ 13 ]. Despite the promising results, including clinical trials, none of these alternative therapies is being used in celiac disease [ 5 ].…”
Section: Introductionmentioning
confidence: 99%